Peranan Hukum Dalam Mewujudkan Kesejahteraan Masyarakat Indonesia - Arini Nova Istiqomah; Yasmine Amira Uzhma; Syifa Fadilah (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
The Republic of Indonesia is a legal state where power is subject to law. The consequence of the rule of law is that law has the highest position in government. "Ubi Societas Ibi Ius", When there is society there is law. The aim of establishing a state is to create social welfare which the government as state administrator formulates in responsive, aspirational and progressive legislation in accordance with the interests of society. The role of law in realizing social welfare must be visible in the material of the law and the moral integrity of law enforcement officers (law actors), especially judges, when adjudicating cases.